Justice and the Grievance Procedure in the Federal Public Service - Moore, William (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The research findings presented here indicate that justice is deterred because of legislative restrictions that preclude certain grievance issues from adjudication.